The Effect Equalization Funds, Capital Expenditures, Audit Findings, and Local Original Revenues on The Financial Performance of District or City Local Governments in Aceh Province - Cut Risa Mahfuza; Aliamin Aliamin; Darwanis Darwanis (Return : Study of Management, Economic and Bussines, 2023)
A study is carried out with a specific purpose as is the case with this study to look for the influence of independent variables on partially or simultaneously bound variables. In a study, there must be samples used by samples in the study, namely as many as 23 districts and 5 cities in Aceh with the number of audits for the 2015-2019 period of as many as 15 reports. After testing after all the data is collected, it is produced that simultan all independent variables affect the dependent variable, while partially all independent variables one by one also affect the dependent variable.